The profile of junior high school students’ problem solving in answering the content TIMSS test of algebra on ideal problem solving - Maria Krissanti; Tri Nova Hasti Yunianta (STKIP PGRI Banjarmasin, 2020)
This research aims to determine the profile of students' problem solving in solving TIMSS algebraic content based on IDEAL problem solving (I-Identify problems, D-Define goals, E-Explore possible strategies, A-Anticipate outcomes and actions, and L-Look back and learn ) in class VIII students at Christian Middle School 2 Salatiga. This research is a qualitative research. There are 3 multiple choice questions TIMSS algebra content with the topic of patterns, forms of algebra, as well as equations and functions. The selection of subjects in this study using purposive sampling obtained as many as 3 subjects. Data collection techniques used were tests, interviews, and documentation. Analysis of the data used is the IDEAL problem solving indicator Based on the results of tests and interviews, it shows that some subjects have been able to carry out the stages of problem solving appropriately and coherently, but some subjects are also lacking in the Explore possible strategies and Look back and learn stages.